From Conception To Connection: Phenomenological Inquiry On Spiritual Health During Pregnancy And Early Motherhood - Yadav, Kanak; Kaur, Raskirat (Journal of Neonatal Surgery, 2025)
Pregnancy is paramount phase in women’s life as her life face transformation physically, emotionally, psychologically and socially that determines her overall wellbeing and actions as an expectant mother towards the growth of the child in womb as both are connected to one another consciously. Spiritual health is the capacity to connect with oneself by taking the practical steps in direction of self-care, nurturance, actualizing the purpose by taking responsibility of the lifestyle and mindset. Spiritual Health in the phase is essential to be reviewed as it would provide the dimensions that are essential for personal growth and development by balancing the physical, psychological and social aspects of the journey. The present analysis provides the interpretative phenomenological analysis on understanding in terms of maternal-fetal attachment that helps mother and child to connect with one another by providing the sense of responsibility towards the budding life within. Spirituality and faith have a significant impact on how one develops a relationship with oneself, improving one's sense of self-worth, confidence, and capacity to respond positively to both internal and external challenges. Understanding of personal dimensions by the pregnant women makes her sensible towards her decisions for the fetal health and her subjective wellness. For the purpose of the research secondary data analysis, Semi-structured interview with pregnant woman and with a new born mother have been incorporated to understand the nuances of spiritual health in depth. Through the qualitative analysis it has been found that the women’s focus on her spiritual health enhances her quality of life and personal efficiency.